Novel treatment options for acute hepatic porphyrias - Wang, Bruce (Curr Opin Gastroenterol, 2021)
PURPOSE OF REVIEW: Acute hepatic porphyrias (AHP) are a group of rare diseases that are characterized by episodic acute neurovisceral pain episodes caused by abnormal accumulation of the neurotoxic porphyrin precursor delta-aminolevulinic acid (ALA). Patient with frequent recurrent acute attacks have been difficult to treat and these patients sometimes require liver transplantation. Recent developments in siRNA-based therapy led to the development of an effective prophylactic treatment for patients with frequent recurrent attacks. This review will describe treatment options for AHP and highlight management in light of new treatment option. RECENT FINDINGS: Givosiran is a novel siRNA-based therapy targeted specifically to hepatocytes to inhibit ALA synthase 1, the first and rate-limiting step in heme biosynthesis. Patients with frequent recurrent attacks treated with givosiran had durable normalization of ALA and significantly reduced numbers of acute attacks and need for hemin treatment. The overall safety profile for givosiran was comparable to placebo and the drug was recently approved by the FDA for treatment of AHP patients. SUMMARY: Givosiran is an effective treatment for prevention of acute porphyria attacks in AHP patients with frequent recurrent attacks.